Stigma and suffering : a theological reflection within the HIV/AIDS pandemic from the perspective of a theologia resurrectionis - Heymans, Frederik J. (Stellenbosch : Stellenbosch University, 2008)
Thesis (MTh)--Stellenbosch University, 2008.